2011
DOI: 10.1063/1.3540679
|View full text |Cite
|
Sign up to set email alerts
|

Proper orthogonal decomposition analysis of vortex dynamics of a circular cylinder under synthetic jet control

Abstract: Articles you may be interested inComparative analysis of low-and high-swirl confined flames and jets by proper orthogonal and dynamic mode decompositions Phys. Fluids 26, 065109 (2014); Interaction of a synthetic jet with the flow over a low aspect ratio cylinder Phys. Fluids 25, 064104 (2013);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(70 citation statements)
references
References 40 publications
9
58
0
3
Order By: Relevance
“…It can be shown that combining the u-and v-based POD results leads to the same results as obtained with the velocity-based POD carried out above. This is consistent with Feng et al (2011) who showed that the POD analysis-based one-velocity component only is appropriate for investigating the near wake.…”
Section: Podsupporting
confidence: 92%
See 1 more Smart Citation
“…It can be shown that combining the u-and v-based POD results leads to the same results as obtained with the velocity-based POD carried out above. This is consistent with Feng et al (2011) who showed that the POD analysis-based one-velocity component only is appropriate for investigating the near wake.…”
Section: Podsupporting
confidence: 92%
“…On the contrary, the velocity-based POD performed in the same flow fields exhibited such a high relative contribution in the most dominant mode (e.g., 30-40 %), showing that the flow is highly organized. In addition, Feng et al (2011) applied both the vorticity-based POD and the velocity-based POD to the wake of a circular cylinder with synthetic jet control and showed that the POD results based on streamwise and vertical velocities are similar to those from the vorticitybased POD for different vortex shedding regimes. It thus seems that the type of POD that is better suited for extracting the dominant structures may depend on the particular flow.…”
Section: Introductionmentioning
confidence: 50%
“…The POD, a flow field analysis method, is a tool that is used to overcome this difficulty. Based on this POD and its analysis of the spatiotemporal characteristics [23,27], it will be more effective to extract the coherent vortical structures and understand the mechanism of the unsteady flow control. The POD method is briefly discussed.…”
Section: Flow Field Analysis Methods (Pod)mentioning
confidence: 99%
“…It is an effective way to extract the dominant structures in turbulent flow based on the turbulent energy rank. Feng [9] used POD method to acquire the vortex dynamics of a circular cylinder controlled by a synthetic jet. The coefficient by POD and corresponding dominant frequency can reveal the characteristics of the flow mode.…”
Section: Introductionmentioning
confidence: 99%